Development of an Internet of Things (IoT) System for Real-Time Monitoring and Control of Moringa Powder Processing. - AMRAN, ROZALINA (Journal of System and Computer Engineering, 2025)
Moringa is a widely recognized food plant in Indonesia due to its numerous health benefits and availability across various regions. One of its processed forms is moringa leaf powder. However, the production process is relatively challenging, primarily due to limited human resources and the time-consuming nature of manual processing. With advancements in technology, these challenges can be addressed through the application of Internet of Things (IoT) systems in the production process. This study aims to design and implement an IoT-based monitoring and control information system using the waterfall development method, which includes the stages of requirements analysis, system design, implementation, testing, and evaluation. The resulting system integrates various sensors, devices, and a NodeMCU microcontroller to automate the production process. The system is connected to the Firebase platform and an Android application, enabling efficient monitoring and control. The primary components used include a DHT-11 temperature and humidity sensor, ultrasonic sensor, Loadcell sensor, MG996 servo motor, adapter, blender, and heating box. The results demonstrate that this system can serve as a modern, technology-based model for efficient moringa plant processing.